2002
DOI: 10.1007/s001980200120
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Parathyroid Hormone-Related Protein and Vascular Endothelial Growth Factor in Human Osteoblastic Cells

Abstract: Osteogenesis and angiogenesis occur in a coordinated manner in skeletal tissue, so that impaired angiogenesis is associated with decreased bone formation in aged subjects. However, the interaction between bone endothelium and osteoblastic cells is poorly understood. Parathyroid hormone-related protein (PTHrP), a bone factor which modulates osteoblastic cell growth and/or differentiation, stimulates vascular endothelial growth factor (VEGF), a potent angiogenic factor, in primary cultures of human osteoblastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 32 publications
2
21
0
2
Order By: Relevance
“…Furthermore, the onset of these changes occurred earlier in PAM than in NPAM. An age-related decrease in PTHrP mRNA levels in the mouse long bones is consistent with previous findings in human osteoblastic cells derived from hip and knee of elderly donors (Martinez et al 2002). It has previously been reported that a decrease in Wnt pathway activation occurs with aging (Almeida et al 2007a).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the onset of these changes occurred earlier in PAM than in NPAM. An age-related decrease in PTHrP mRNA levels in the mouse long bones is consistent with previous findings in human osteoblastic cells derived from hip and knee of elderly donors (Martinez et al 2002). It has previously been reported that a decrease in Wnt pathway activation occurs with aging (Almeida et al 2007a).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, this age-related diminution also occurred for the gene expression of OC, a late osteoblast differentiation marker (Pockwinse et al 1992;Zhang et al 2010). It has been demonstrated that PTHrP production-an important modulator of bone formation and remodeling in adult bone (Bisello (Martinez et al 2002). Here, we found that PTHrP gene expression was significantly downregulated in both NPAM and PAM with aging.…”
Section: Resultssupporting
confidence: 59%
“…Other authors have reported an age-related decrease in the secreted levels of VEGF in osteoblasts [16] and an increase in VEGF and a decrease in parathyroid hormone-related protein after vitamin D incubation. Since VEGF is a key factor of angiogenesis, we hypothesized a decrease in VEGF in the early stage of ON and an increase in the late stage of ON.…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, aged or diseased patients may have distinct capabilities for neovascularization. For example, diabetic patients have reduced angiogenic responsiveness [77,78] as do aged subjects [79]. This could result from impaired growth factor/receptor signaling [80], a reduction in endothelial cell responsiveness, or a reduction of the number of circulating progenitor cells [81,82].…”
Section: Further Considerationsmentioning
confidence: 99%